Penggunaan Nasogatric Tube Berhubungan dengan Terjadinya Pneumonia - Meriyanti, Meriyanti; Rohana, Nana; Windyastuti, Windyastuti (Jurnal Ners Widya Husada, 2017)
Penggunaan Nasogatric Tube merupakan salah satu faktor terjadinya pneumonia. Pneumonia merupakan proses inflamasi pada parenkim paru yang biasanya berhubungan dengan peningkatan cairan alveolar dan interstisial. Pneumonia adalah infeksi nosokomial tertinggi ke dua angka kejadiannya. Komplikasi penggunaan nasogatric tube dapat mengakibatkan pneumonia aspirasi. Penelitian kuantitatif dengan jenis observasional analitik dan menggunakan rancangan cross sectional. Pengambilan sampel dengan tekhnik consecutive sampling  dengan jumlah sampel sebanyak 17 responden. Responden yang diambil adalah responden yang menggunakan NGT >48 jam. Pengumpulan data menggunakan lembar observasi. Analisis ini menggunakan uji statistik Fisher Exact. Ditemukan kejadian pneumonia sebanyak 13 orang (76,5%). Berdasarkan uji statistik fisher exact didapatkan hasil p value 0,022 < α= 0,05.dan OR = 0,028. Ada hubungan penggunaan nasogatric tube dengan terjadinya pneumonia. Kata kunci: penggunaan nasogatric tube, terjadinya pneumonia USE OF NASOGASTRIC TUBE IS RELATED TO PNEUMONIA ABSTRACTNasogatric Tube is one of the factors of the occurance of pneumonia. Pneumonia is an inflammatory process in the pulmonary parenchyma that is usually associated with elevated alveolar and interstitial fluids. Pneumonia is the highest nosocomial infection in both cases. Complication of using nasogatric tube lead aspiration pneumonia. The purpose of this study was to determine the relationship of nasogatric tube use with the incidence of pneumonia in ICU RSUD. Dr. Adhyatma, MPH Semarang. a quantitative study was applied an analytic observational study using cross sectional design. The sample method used was a consecutive sampling technique gain of 17 respondents. Respondents were respondents who used NGT >48 hours. Taking data with observation sheets. This analysis uses Fisher Exact statistic test. The incidence of pneumonia was 13 people (76,5%). Based on statistical test shows that there is relationship of nasogatric tube usage with the incidence of pneumonia in ICU RSUD. DR. Adhyatma, MPH Semarang, with p value 0,022 <α = 0,05 and OR = 0,028. Ho is rejected Ha accepted, it’s means there is relationship use nasogatric tube with the incidence of pneumonia. Keywords: nasogatric tube, pneumonia incidence